Contribution of Vidhatha Resource Center for small industries and handicrafts; a study focusing on the Akurana area of the Kandy district - M.N. Nuska Banu; M.A.F. Afra (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
Most people in the world depend on industrial activities. People who were aware of the need for industrial activities after industrial revolution are still enjoying its benefits to this day. Profit or loss they receive according to their capital. It is most commendable thing that the contribution of the way of government and non-government organizations based on that to promote industrial initiatives in developing countries like Sri Lanka. Accordingly, the study is aimed at developing the small scale industries in Akurana and Vidhatha Resource Centre which provides it to the people with a view to developing the villages found in Sri Lanka in industrial ventures, and identified small scale industries in Akurana area in Kandy district. The main objective of the survey is to provide information on the Vidhatha Resource Centre for children and seniors in the Akurana area and to be a partner in improving the Sri Lankan economy, and the purpose of the study is to bring information about the Vidhatha Resource Centers, and its services to the public. Data were collected through interviews with up to 50 people living in the area. The results were obtained from the interviews with Vidhatha Resource owners and entrepreneurs. There are currently total 257 Vidhatha Resource Centers operating in Sri Lanka, and there are 19 Vidhatha Resource Centers in Kandy district, and only one Vidhatha Resource Centre is in Akurana. Although there is a lot of industry in Sri Lanka, Vidhatha Resource Centre in Akurana is mostly used for candle making, food preparation, nutmeg and other products. In addition, specific people from Grama-Nilathari section are recruited for the software courses and hardware courses. These Vidhatha Resource Centers are also very useful for the common people to create self-employment opportunities, and for the people involved in self-employment to improve their quality of life. By upgrading such resource centers island wild, even ordinary people are more likely to reap the greatest benefits. Doing so, can build a sustainable prosperous Sri Lanka in future. Keywords: small scale industry, Vidhatha Resource Centre, economy, entrepreneur, people